An assessment of customer service in business-to-business relationships - Zolkiewski, Judy; Lewis, Barbara; Yuan, Fang; Yuan, Jing (The Journal of services marketing, 2007)
Purpose - The purpose of this paper is to develop a deeper understanding of customer service service quality in business-to-business contexts.Design methodology approach - An in-depth case study was used to discover the perceptions of both key individuals in the supplying company and key customers.Findings - The paper shows that that customer service service quality in a business-to-business context is a complex and multifaceted issue, the different parties in a relationship have differing perceptions of what constitutes service quality and that actors from the wider network can have an impact on perceptions of service quality.Research limitations implications - This work is tentative in nature so it is not possible to generalise the findings to a wider context. However, it suggests that this area needs much more detailed and in-depth investigation.Practical implications - Managers need to be aware of the complexity of customers' service quality perceptions in a business-to-business context. They must consider dynamics, actions of other actors and how best to demonstrate their expertise and experience.Originality value - The findings of this research, although only exploratory, are significant because they are one of the few pieces of research into business-to-business service quality in which perceptions of quality from both sides of the dyad are collected and analysed.